2012
DOI: 10.4028/www.scientific.net/amr.507.21
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Impurity Atoms on the Structural and Electronic Properties of Au<sub>3</sub> Clusters

Abstract: With density functional theory, the structural and electronic properties of Au3 and Au2M (M=Ag, Cu, Pd and Pt) clusters have been studied. The structural results indicate that by substituting one Au atom with M atom, the corresponding geometries are changed slightly. To investigate the electronic properties, bonding properties and highest occupied molecular orbital (HOMO) were observed. It is found that most trends in Au2Pd and Au2Pt are similar and it also happens in the other two doped clusters. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…21 For example, Li et al found that doping Ag, Cu, Pd or Pt atoms in small size Au clusters can change their electronic properties, which is conducive to the analysis of adsorption problems. 22 Moreover, the electronic properties and magnetic properties can be adjusted by doping single O and H atoms in small Ni clusters. 23 In order to make the structures and dynamics of binary alloy clusters more reasonable, more calculations or simulations are needed to verify and adjust their structures and compositions.…”
Section: Introductionmentioning
confidence: 99%
“…21 For example, Li et al found that doping Ag, Cu, Pd or Pt atoms in small size Au clusters can change their electronic properties, which is conducive to the analysis of adsorption problems. 22 Moreover, the electronic properties and magnetic properties can be adjusted by doping single O and H atoms in small Ni clusters. 23 In order to make the structures and dynamics of binary alloy clusters more reasonable, more calculations or simulations are needed to verify and adjust their structures and compositions.…”
Section: Introductionmentioning
confidence: 99%